THE MODIFIED FERRIMAN-GALLWEY SCORE AND HIRSUTISM AMONG FILIPINO WOMEN - Ilagan, Ma. Karen Celine; Paz-Pacheco, Elizabeth; Totesora, Darwin; Clemente-Chua, Lyra Ruth; Jalique, Jundelle (Journal of the ASEAN Federation of Endocrine Societies, 2022)
INTRODUCTION The modified Ferriman-Gallwey (mFG) score is the gold standard in the clinical evaluation of hirsutism, a common manifestation of hyperandrogenism. Racial variations in terminal hair growth limit this tool. Ideally, race-specific mFG scores for hirsutism should be established. This study aimed to determine the mFG cut-off score among Filipino women and its association with biochemical hyperandrogenism. METHODOLOGY A total of 128 Filipino females were included in this prospective cross-sectional study and divided into 2 groups: PCOS (n=28) and non-PCOS (n=100). Polycystic ovary syndrome (PCOS) was diagnosed using the 2003 Rotterdam Criteria while non-PCOS subjects were healthy controls conveniently sampled from the general population. They underwent mFG score determination, ovarian ultrasound by a single sonographer, and hormone testing. The mFG cut-off score was determined based on the 95th percentile in the non-PCOS group. Logistic regression was used to analyze the relationship of the determined mFG score with biochemical hyperandrogenism. RESULTS Normal values of the total mFG score is between 0 and 7. Using a cut-off score of 7, a higher proportion of hirsute women were observed in the PCOS group (17.9% vs. 5.0%, p=0.025). Elevated calculated free testosterone (cFT) was also significantly associated with hirsutism (odds ratio, 5.9; 95% CI, 1.4 – 23.8; p=0.013). CONCLUSION A score of 7 and above represents hirsute women in this population. Hirsute women are more likely to have elevated cFT.